Legal Protection for Children as Perpetrators of Violent Crimes in the Investigation Process - Qamariatul Arini; M. Hidayat; Bastianto Nugroho (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
The aim of the research is to find out what factors influence the implementation of legal protection for children who are perpetrators of violent crimes in the investigation process at the Sumenep Resort Police. Legal research using normative legal research methods in drawing conclusions using deductive thinking methods. Starting with drawing conclusions based on general things to specific things. By comparing primary legal materials and secondary legal materials, problems can be narrowed down from general to specific. Results There are 3 factors that become obstacles in the legal protection of children at the investigation stage. The first is that recidivism is a consideration factor in giving heavier sentences to child offenders. Second, the reporters and/or victims feel that justice is fulfilled if the child perpetrator is detained, tried and imprisoned. Third, the lack of adequate child care places is an obstacle for children to socialize with other children when parents work or are not at home, especially in the Sumenep Police Law area.